Interacting C/EBPg and YBP regulate DNA methyltransferase 1 expression in Bombyx mori embryos and ovaries. (July 2021) - Lyu, Hao; Xu, Guanfeng; Peng, Xuezhen; Gong, Chengcheng; Peng, Yuling; Song, Qisheng; Feng, Qili; Zheng, Sichun
Abstract: DNA methylation is an important epigenetic modification. DNA methyltransferases (Dnmts), which catalyze the formation of 5-methylcytosine, play a role in ovarian and embryonic development in some insects. However, the underlying mechanism of Dnmt in mediating ovarian and embryonic development remains unclear. In this study, the regulation and function of Bombyx mori Dnmt1 were investigated. By progressively deleting the sequence upstream of Dnmt1, a region located between −580 and −560 region from the transcription initiation site was found to have the most transcriptional activity. Electrophoretic mobility shift assay and chromatin immunoprecipitation demonstrated that transcription factor Y box binding protein (YBP), a homolog of human Y box binding protein 1 (YBX1), bound to the −580 to −560 region. YBP knockdown and overexpression in a Bombyx cell line indicated that YBP activates Dnmt1 expression. Furthermore, GST-pulldown and co-immunoprecipitation demonstrated that YBP and ovarian CCAAT/enhancer binding protein (C/EBPg) could bind each other. Simultaneous knockdown of C/EBPg and YBP was more effective than single-gene RNAi in inhibiting Dnmt1 expression and reducing the hatching rate. These results demonstrated that the interaction of C/EBPg and YBP activated Dnmt1 expression. Correlated with the expression profiles of the studies genes, our results suggest that high-level expression and interaction of C/EBPg and YBP in ovaries and embryos enhance the expression of Dnmt1, thus ensuring high reproduction rate in B. mori . Highlights: Y box binding protein (YBP) enhances expression of DNA methyltransferase 1 ( Dnmt1 ) in Bombyx. YBP binds to an enhancer element upstream of the Dnmt1 gene. CCAAT/enhancer binding protein (C/EBPg) promotes Dnmt1 expression by interacting with YBP. Knockdown of YBP, C/EBPg, and Dnmt1 reduces the hatch rate of Bombyx embryos.